The relationship between resource, capability, innovation, logistics performance, and competitive advantage. - Zuraimi Abdul Aziz (2017)
Logistics Service Providers (LSPs) are now facing major challenges to remain competitive as the deregulation and liberalization increase. This factor leads to the increasing of competition in the market. Sustaining competitive position for LSPs are a paramount important in global and domestics business and it would achieve by improving a firm’s performance and getting a position of competitive advantage over its rivalry. To investigate this issue, this study has examined the competiveness of LSPs by measuring the logistics performance and competitive advantage, which focusing on LSPs sector in Malaysia. Grounded by the Resource-based View (RBV) and Dynamic Capability theory, this study proposes a framework by decomposing Resources, Capabilities and Logistics Innovation as a factor, and Logistics Performance as a mediator. A total of 126 firms from LSPs in Malaysia have participated in this study. Data for all the study variables were collected through mail survey questionnaires. Partial Least Square Structural Equation Modelling (PLS-SEM) was the main statistical techniques used in this study. The findings indicated that only two mains factors, namely resources and capabilities were found to have a significant effect on logistics performance and competitive advantage. Whereas, logistics innovation factor insignificantly influence the logistics performance and competitive advantage of LSPs. The results also established the presence of mediation effect of logistics performance between independent variable and dependent variable except for logistics innovation. Overall, the results indicate that the model provides a good understanding of the factors that influence the competitiveness of LSPs market. Based on the findings, the theoretical and practical implications of the study as well as limitations are also discussed. In the future, apart from strengthening the resources and capabilities, it is desirable for the LSPs in Malaysia to enhance the innovation in order to compete in the market.